Clinical relevance of the de novo production of anti‐HLA antibodies following intestinal and multivisceral transplantation. (16th January 2014) - Gerlach, Undine A.; Lachmann, Nils; Sawitzki, Birgit; Arsenic, Ruza; Neuhaus, Peter; Schoenemann, Constanze; Pascher, Andreas
Summary Despite a negative pretransplant cross‐match, intestinal transplant recipients can mount humoral immune responses soon after transplantation. Moreover, the development of donor‐specific anti‐HLA antibodies (DSAs) is associated with severe graft injury. Between June 2000 and August 2011, 30 patients (median age 37.6 ± 9.8 years) received isolated intestinal transplantations (ITX, n = 18) or multivisceral transplantations (MVTXs, n = 12) at our center. We screened for human leukocyte antigen (HLA) antibodies pre‐ and post‐transplant. If patients produced DSAs, treatment with plasmapheresis and intravenous immunoglobulin (IVIG) was initiated. In the event of DSA persistence and/or treatment‐refractory rejection, rituximab and/or bortezomib were added. Ten patients developed DSAs and simultaneously showed significant signs of rejection. These patients received plasmapheresis and IVIG. Eight patients additionally received rituximab, and two patients were treated with bortezomib. DSA values decreased upon antirejection therapy in 8 of the 10 patients. The development of DSAs following ITX is often associated with acute rejection. We observed that the number of mismatched antigens and epitopes correlates with the probability of developing de novo DSAs. Early diagnosis and therapy, including B‐cell depletion and plasma cell inhibition, are crucial to preventing further graft injury.